Pembatalan Pernikahan Akibat Penipuan Identitas Poligami - Helmi Yusuf (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This research examines cases of marriage annulment due to polygamous identity fraud in the Religious Court of Bandung. The study aims to analyze the considerations and legal basis of the Bandung Religious Court in deciding first-instance, appellate, and cassation cases related to the annulment of marriages due to polygamous identity fraud. The research method used is document analysis based on court decisions related to such cases. The data analyzed include the judges' considerations, legal foundations, and factors influencing the court's decisions. The findings reveal that the Bandung Religious Court considers aspects such as the validity of the marriage, the domicile of the parties involved, witness testimonies, and the timing of the annulment request. The legal basis referred to includes Article 73 letter d of the Compilation of Islamic Law and Article 27 paragraph 3 of Law No. 1 of 1974. On the other hand, the appellate and Supreme Courts consider the presence of mediators and the social implications of marriage annulment.